A Rare Case of Radiation-Induced Osteosarcoma of the Ethmoid Sinus. (2011) - Alzahrani, Musaed; Robier, Alain; Pointreau, Yoann; Bakhos, David
Abstract : Radiation therapy has been recognized as a useful modality of treatment in head and neck malignant tumors. However, radiation over 10 Gy may predispose to secondary tumors. Radiation-induced osteosarcoma of the ethmoid sinus is unusual. These tumors may present long after radiation with epistaxis. Computed tomography, magnetic resonance imaging, and biopsy are the modalities of diagnosis. We report a case of radiation-induced osteosarcoma of the ethmoid sinus 9 years after initial exposure. We describe the clinical presentation, the radiological findings, and the management.